Low Achiever Students’ Perception on the Use of Higher Order Thinking Skills (HOTS) in Reading Comprehension (International Journal of Academic Research in Progressive Education and Development, 2020)
Reading activity helps students to acquire Higher Order Thinking Skills (HOTS) in reading comprehension as one of the important elements in learning a language. Most students are aware of the implementation of HOTS in learning the language skills, including reading. However, low achiever students' perceptions on the use of HOTS are slightly different. This research aims to identify findings on students' perception of the use of HOTS in reading comprehension among low achievers. Data was gained from a questionnaire survey of 30 low achiever second language students from a school in Bagan Serai, Malaysia. This study shows that the use of HOTS is beneficial and helps low achiever students to gather good information on their reading comprehension. The results of this study are hoped to gain good perception among low achiever students as feedback whether HOTS can be one of the methods to enhance their reading comprehension.
Keywords: Low Achiever, Reading Comprehension, Thinking Skill, Perception